Mentoring as an opportunity to improve research and cancer care in Latin America (AAZPIRE project). Issue 6 (24th November 2020) - Angel, Martín Osvaldo; Colombo Bonadio, Renata; Harada, Guilherme; Waisberg, Federico; Enrico, Diego; Arrieta, Oscar; Corrales, Luis; Martin, Claudio; Werustky, Gustavo; Barrios, Carlos; Ricaurte, Luisa; Cardona, Andres F.
Abstract : Effective networking and mentoring are critical determinants of professional satisfaction and success in oncology. There are multiple benefits associated with established mentoring programs. However, these are scarce in Latin America (LATAM). The AAZPIRE project meeting was held to encourage the discussion of mentorship strategies in our region, to create new learning frameworks, and improve cancer care. A group of 30 young oncologists and investigators, together with seven members of LACOG and CLICaP experts of 8 LATAM countries, were reunited to share views and define opportunities, barriers, and possible solutions to implement mentorship programs in LATAM. For each of the mentioned topics, key points were obtained by consensus, and a literature review was conducted to support group conclusions. This article analyses mentoring in LATAM countries and its role on promoting leadership. It will address conceptual frameworks, limitations, and opportunities from the perspectives of both mentor and mentee. The creation of regional and international group stimulation programs and joint projects that impact health policies are attractive, starting points to implement mentorship scenarios.